Sulfur-containing benzofurans and α-pyrones from the mangrove-derived fungus Talaromyces sp. WHUF0341 - Ruohan Zhang; Jinxin Zhang; Ruiyun Huo; Yaxin Xue; Kui Hong; Ling Liu (Frontiers in Marine Science, 2022)
Two new sulfur-containing benzofurans, talarobenzofurans A and B ( 1 and 2 ), one new benzofuran talarobenzofuran C ( 3 ) and two new α -pyrones talaropyrones A and B ( 5 and 6 ), along with five known compounds eurothiocin A ( 4 ), nodulisporipyrone A ( 7 ), peniazaphilin B ( 8 ), ramulosin ( 9 ) and 6-hydroxyramulosin ( 10 ) were isolated and identified from the culture extract of the mangrove-derived fungus Talaromyces sp. WHUF0341 guided by OSMAC (one strain-many compounds) strategy. Their structures were established by extensive spectroscopic data analysis, the modified Mosher’s method and electronic circular dichroism (ECD) calculations. Structurally, compounds 1 and 2 possesed the unique thioester moiety derived from benzofuran and 2-hydroxy-3-mercaptopropionic acid, which was rarely-observed in natural products. The α -glucosidase inhibitory and antibacterial activities of the isolated compounds were evaluated. Compounds 3 and 4 exhibited inhibitory effects against α -glucosidase activity with IC 50 values of 48.9 ± 2.16 and 8.8 ± 1.08 µM, respectively. The inhibitory type of 3 on α -glucosidase was determined as non-competitive-type inhibition with K i value of 242.3 μM by using Lineweaver-Burk double reciprocal and Dixon single reciprocal plots. Meanwhile, the binding model of 3 and 4 with α -glucosidase was determined by molecular docking assay. The biosynthetic pathways of compounds 1 − 4 were also proposed. This study suggested that benzofurans 3 and 4 could be potential lead compounds for the hypoglycemic drugs.